High-Pressure Extraction of Antioxidant-Rich Fractions from Shrubby Cinquefoil (Dasiphora fruticosa L. Rydb.) Leaves: Process Optimization and Extract Characterization - Michail Syrpas; Kiran Subbarayadu; Vaida Kitrytė; Petras Rimantas Venskutonis (MDPI AG, 2020)
Dasiphora fruticosa (basionym Potentilla fruticosa) is a shrub, known in traditional medicine for centuries. Due to the wide range of pharmacological effects, interest and applications of D. fruticosa extracts are continually increasing; however, reports on optimization of extraction conditions are scarce. Herein, a multi-step high-pressure extraction process with increasing polarity solvents was developed to isolate valuable fractions from D. fruticosa leaves. Supercritical CO2 extraction recovered 2.46 g/100 g of lipophilic fraction, rich in polyunsaturated fatty acids. Further, pressurized liquid extractions (PLE) with acetone, ethanol, and water were applied to obtain antioxidant-rich higher polarity extracts. Under optimized PLE conditions, the cumulative polar fraction yield was 29.98 g/100 g. Ethanol fraction showed the highest yield (15.3 g/100 g), TPC values (148.4 mg GAE/g), ABTS•+, and DPPH• scavenging capacity (161.1 and 151.8 mg TE/g, respectively). PLE was more efficient than conventional solid-liquid extraction in terms of extraction time, extract yields, and in vitro antioxidant capacity. Phytochemical characterization of PLE extracts by UPLC-Q-TOF-MS revealed the presence of hyperoside, ellagic acid, among other health beneficial phenolic substances. Τhis study highlights the potential of high-pressure extraction techniques to isolate antioxidant-rich fractions from D. fruticosa leaves with multipurpose applications, including the prevention and treatment of chronic diseases.